Microbial dynamics and key sensory traits of laboratory-scale co-fermented green olives (Olea europaea L. cv. Ascolana tenera) and sea fennel (Crithmum maritimum L.). (December 2022) - Maoloni, Antonietta; Cardinali, Federica; Milanović, Vesna; Osimani, Andrea; Garofalo, Cristiana; Ferrocino, Ilario; Corvaglia, Maria Rita; Cocolin, Luca; Aquilanti, Lucia
Abstract: Table olives ( Olea europaea L.) are one of the most important fermented vegetables worldwide, whereas sea fennel ( Crithmum maritimum L.) represents an emerging food crop, characterized by interesting nutritional and sensory qualities. Both are characterized by a high concentration of bioactive compounds with health beneficial effects. Thanks to these features, table olives and sea fennel undoubtedly represent two valuable ingredients for the manufacture of innovative vegetable preserves. Given these premises, the present study was aimed at exploring the co-fermentation of green olives and sea fennel to produce laboratory-scale prototypes of innovative high value preserves. To this end, the effects of two recipes, two standard methods for production of table olives, and two fermentation microbiota (resident or inoculated) were assessed. The prototypes were evaluated for their microbial dynamics as well as for key sensory traits by a panel of trained assessors. During the fermentation, all the prototypes showed a progressive pH reduction. Mesophilic lactobacilli, mesophilic lactococci, and yeasts were the main microbial groups at the end of the fermentation, while Enterobacteriaceae decreased during fermentation. Metataxonomic analysis revealed an evolution of the microbiota, with Lactiplantibacillus plantarum dominating in all the prototypes in the late stage of fermentation, irrespective of the recipe, processing method, and starter inoculation. A greater crunchiness and lower fibrousness were perceived in the Greek style prototypes, which were preferred than Spanish style prototypes by trained panelists. Highlights: The co-fermentation of green table olives and sea fennel sprouts was explored. Two processing methods were applied with or without a selected starter. Lactiplantibacillus plantarum dominated the late stage of the fermentation. Greek style prototypes: more crunchy, less fibrous and with a greater acceptability.